Description Of Periodontal Tissue Severity Level In Diabetes Mellitus Patients At Dahlia Makassar Health Center - Abdullah, Rusli; Hitipeuw, Anthoneta Johanna; Syarief, Syarifah Wahyuni Al; Putri, Safridha Kemala; Mahyudin, Mahyudin; Prehananto, Herlambang (International Journal of Health Sciences, 2024)
Diabetes mellitus or what is better known to the general public as diabetes is a degenerative disease that can be accompanied by chronic or acute complications and is a non-communicable disease. Diabetes Mellitus is a systemic disease that is often found in developed and developing countries, one of which is our country, Indonesia. This is caused by some Indonesian people having an unhealthy lifestyle and a lack of physical activity such as exercising. The aim of this study was to determine the level of severity of periodontal tissue in Diabetes Mellitus sufferers who visited the Community Health Center dental clinic. The descriptive research method is to determine the level of severity of Periodontal Tissue in Diabetes Mellitus sufferers at the Community Health Center. The results show that all Diabetes Mellitus sufferers have problems with their periodontal tissue and most of them are at a severe level. Based on the results of the research and discussion above, it can be concluded that all Diabetes Mellitus sufferers have problems with their periodontal tissue and as many as 60% of them are at a severe level of severity.